Reduced Morbidity and Mortality Associated With Minimally Invasive Single-vessel Coronary Artery Bypass Compared With Conventional Sternotomy. Issue 5 (7th May 2023) - Cain, Michael T.; Joyce, David L.; Szabo, Aniko; Wu, Ruizhe; Kohmoto, Takushi; Joyce, Lyle D.; Pearson, Paul J.
Abstract : Objective: We aimed to describe the safety and clinical benefits of minimally invasive, nonsternotomy coronary artery bypass grafting (MICABG) using data from The Society of Thoracic Surgeons (STS) National Database. Background: MICABG has gained popularity, owing to expected lower perioperative morbidity and shorter recovery. Despite this, concerns remain regarding anastomotic quality and the validity of proposed perioperative benefits. Methods: We queried the STS National Database for all patients who underwent single-vessel coronary artery bypass grafting (CABG) from January 2014 to December 2016 to compare outcomes of MICABG with conventional CABG. Patients who underwent concomitant or emergent procedures were excluded. Propensity-weighted cohorts were compared by operative approach with adjustment for variability across institutions. Results: Of 12, 406 eligible patients, 2688 (21.7%) underwent MICABG, and 9818 (78.3%) underwent conventional CABG. Propensity weighting produced excellent balance in patient characteristics, including completeness of revascularization, body mass index, and STS predictive risk scores. MICABG was associated with significant reduction of in-hospital mortality [odds ratio (OR)=0.32, absolute reduction (AR)=0.91%, P <0.0001]; 30-day mortality (OR=0.51, AR=0.88%, P =0.001), duration of ventilation (8.62 vs 12.6 hours, P <0.0001), prolonged hospitalization (OR=0.77, AR=1.6, P =0.043), deep wound infection (OR=0.33, AR=0.68, P <0.004), postoperative transfusions (OR=0.52, AR=7.7%, P <0.0001), and STS composite morbidity (OR=0.72, AR=1.19%, P =0.008). Subgroup analysis of only off-pump left internal mammary artery-left anterior descending CABG showed similar findings. Major adverse cardiac events and graft occlusion did not differ between groups. Conclusions: MICABG is associated with lower mortality and perioperative morbidity compared with conventional sternotomy CABG. MICABG may have a role in treating single-vessel disease.